(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2026)
The adoption of the Law of the Republic of Uzbekistan "On Weapons" established the legal basis for the licensing and permitting system in the sphere of weapons circulation. The introduction of this system significantly strengthened state regulation of relevant legal relations and led to a significant increase in both the types of weapons permitted for civilian circulation and the number of permits. At the same time, the workload of employees of the control and licensing units of internal affairs agencies, as well as of employees of public order protection units (hereinafter referred to as PLOPS employees) and prevention inspectors, who are responsible for state and departmental oversight functions in this area, has increased significantly.